Fecal Calprotectin to Detect Inflammatory Bowel Disease in Juvenile Idiopathic Arthritis. - Ferrara, Giovanna; Pastore, Serena; Sancin, Lara; Torelli, Lucio; Radillo, Oriano; Bramuzzo, Matteo; Bibalo, Chiara; Tommasini, Alberto; Ventura, Alessandro; Taddio, Andrea (J Rheumatol, 2018)
OBJECTIVE: This study aimed to test fecal calprotectin (FC) as a screening tool to identify inflammatory bowel disease (IBD) among patients with juvenile idiopathic arthritis (JIA). METHODS: FC level < 100 g/kg was considered normal. Patients with 2 consecutive FC dosage ≥ 100 g/kg underwent endoscopic evaluation. RESULTS: There were 113 patients with JIA enrolled. FC was raised in 7 patients out of 113. All patients had IBD. In 3/7 patients, high FC levels were the only sign consistent with IBD. CONCLUSION: FC is a useful, economical, and noninvasive diagnostic tool to identify JIA patients with underlying IBD.

Flares After Withdrawal of Biologic Therapies in Juvenile Idiopathic Arthritis: Clinical and Laboratory Correlates of Remission Duration. - Simonini, Gabriele; Ferrara, Giovanna; Pontikaki, Irene; Scoccimarro, Erika; Giani, Teresa; Taddio, Andrea; Meroni, Pier Luigi; Cimaz, Rolando (Arthritis Care Res (Hoboken), 2018)
OBJECTIVE: To assess the time in remission after discontinuing biologic therapy in patients with juvenile idiopathic arthritis (JIA). METHODS: We enrolled 135 patients followed in 3 tertiary-care centers. The primary outcome was to assess, once remission was achieved, the time in remission up to the first flare after discontinuing treatment. Mann-Whitney U test, Wilcoxon's signed rank test for paired samples, chi-square tests, and Fisher's exact test were used to compare data. Pearson's and Spearman's correlation tests were used to determine correlation coefficients for different variables. To identify predictors of outcome, Cox regression model and Kaplan-Meier curves were constructed, each one at the mean of entered covariates. RESULTS: The majority of enrolled patients flared after stopping treatment with biologics (102 of 135, 75.6%) after a median followup time in remission off therapy of 6 months (range 3-109 months). A higher probability of maintaining remission after discontinuing treatment was present in systemic-onset disease compared to the rest of the JIA patients (Mantel-Cox χ = 8.31, P < 0.004). In analysis limited to children with JIA with polyarticular and oligoarticular disease, patients who received biologics >2 years after achieving remission had a higher probability of maintaining such remission off therapy (mean ± SD 18.64 ± 3.3 months versus 11.51 ± 2.7 months [P < 0.009]; Mantel-Cox χ = 9.06, P < 0.002). No other clinical variable was significantly associated with a long-lasting remission. CONCLUSION: Children with oligoarticular and polyarticular JIA who stop treatment before 2 years from remission have a higher chance of relapsing after biologic withdrawal.

Chronic nonbacterial osteomyelitis may be associated with renal disease and bisphosphonates are a good option for the majority of patients. - Pastore, Serena; Ferrara, Giovanna; Monasta, Lorenzo; Meini, Antonella; Cattalini, Marco; Martino, Silvana; Alessio, Maria; La Torre, Francesco; Teruzzi, Barbara; Gerloni, Valeria; Breda, Luciana; Taddio, Andrea; et al. (Acta Paediatr, 2016)
AIM: The aim of this Italian study was to describe the clinical features, treatment options and outcomes of a cohort of patients with chronic nonbacterial osteomyelitis (CNO). METHODS: This was a retrospective cohort study. Laboratory data, diagnostic imaging, histological features and clinical course are reported. RESULTS: We enrolled 47 patients diagnosed with CNO. Bone pain was the leading symptom, and multifocal disease was present in 87% of the patients. The majority of the bone lesions were located in the appendicular skeleton (58%). Extraosseous manifestations were present in 34% of the patients, and renal involvement was detected in four patients. Inflammatory indices were increased in 80%, and bone x-rays were negative in 15% of the patients. Nonsteroidal anti-inflammatory drugs (NSAIDs) were the first therapy for all patients, achieving clinical remission in 27%. A good response to NSAIDs was significantly associated with a better prognosis. Bisphosphonates were used in 26 patients, with remission in 73%. Only six patients (13%), all with spine involvement, developed sequelae. CONCLUSION: We found a possible association between CNO and renal disease. Bisphosphonates were more likely to lead to clinical remission when NSAIDs and corticosteroids had failed. Vertebral localisation was the only risk factor for potential sequelae.

Does Teno Torque Virus Induce Autoimmunity After Hematopoietic Stem Cell Transplantation? A Case Report. - Maximova, Natalia; Pizzol, Antonio; Ferrara, Giovanna; Maestro, Alessandra; Tamaro, Paolo (J Pediatr Hematol Oncol, 2015)
Teno Torque virus, member of the family of Anelloviridae, has been associated with many autoimmune diseases such as idiopathic hepatitis, systemic lupus erythematosus, and multiple sclerosis. Its viral load tends to be higher in the bone marrow and in tissues with high turnover rate. We report here a case of an 11-month-old infant affected by acute myeloid leukemia who underwent hematopoietic stem cell transplantation, and after 6 months had autoimmune hepatitis and atopic dermatitis. Extremely high-cytokine IP-10 and eotaxin levels were found in her sera, and serological tests and RT-PCR for viruses showed positive results exclusively for Teno Torque virus.
Keywords: Autoimmune Diseases; Autoimmunity; Dermatitis, Atopic; DNA Virus Infections; DNA, Viral; Female; Hematopoietic Stem Cell Transplantation; Hepatitis; Humans; Infant; Leukemia, Myeloid, Acute; Prognosis; Torque teno virus; Viral Load

More than (Double) Bubble. - Ferrara, Giovanna; Stampalija, Tamara; Codrich, Daniela; Simionato, Cristina; Taddio, Andrea; Travan, Laura (J Pediatr, 2015)
Keywords: Amniotic Fluid; Duodenum; Female; Humans; Infant; Infant, Newborn; Polyhydramnios; Pregnancy; Pregnancy Trimester, Third; Prenatal Diagnosis; Ultrasonography, Prenatal

Acquired long QT syndrome: a focus for the general pediatrician. - Marzuillo, Pierluigi; Benettoni, Alessandra; Germani, Claudio; Ferrara, Giovanna; D'Agata, Biancamaria; Barbi, Egidio (Pediatr Emerg Care, 2014)
Acquired long QT syndrome (LQTS) is a disorder of cardiac repolarization most often due to specific drugs, hypokalemia, or hypomagnesemia that may precipitate torsade de pointes and cause sudden cardiac death. Common presentations of the LQTS are palpitations, presyncope, syncope, cardiac arrest, and seizures. An abnormal 12-lead electrocardiogram obtained while the patient is at rest is the key to diagnosis. The occurrence of drug-induced LQTS is unpredictable in any given individual, but a common observation is that most patients have at least 1 identifiable risk factor in addition to drug exposure. The cornerstone of the management of acquired LQTS includes the identification and discontinuation of any precipitating drug and the correction of metabolic abnormalities, such as hypokalemia or hypomagnesemia. Most of the episodes of torsade de pointes are short-lived and terminate spontaneously. We propose a management protocol that could be useful for the daily practice in the emergency pediatric department to reduce the risk of acquired QT prolongation.
Keywords: Adolescent; Death, Sudden, Cardiac; Electrocardiography; Female; General Practitioners; Humans; Long QT Syndrome; Ondansetron; Risk Factors; Serotonin Antagonists

A comparison of three scales for measuring pain in children with cognitive impairment. - Massaro, Marta; Ronfani, Luca; Ferrara, Giovanna; Badina, Laura; Giorgi, Rita; D'Osualdo, Flavio; Taddio, Andrea; Barbi, Egidio (Acta Paediatr, 2014)
AIM: Pain is a neglected problem in children with cognitive impairments, and few studies compare the clinical use of specific pain scales. We compared the Non-Communicating Children's Pain Checklist Postoperative Version (NCCPC-PV), the Echelle Douleur Enfant San Salvador (DESS) and the Children's Hospital of Eastern Ontario Pain Scale (CHEOPS). The first two were developed for children with cognitive impairment, and the third is a more general pain scale. METHODS: Two external observers and the child's caregiver assessed 40 children with cognitive impairment for pain levels. We assessed inter-rater agreement, correlation, dependence on knowledge of the child's behaviour, simplicity and adequacy in pain rating according to the caregiver for all three scales. RESULTS: The correlation between the NCCPC-PV and the DESS was strong (Spearman correlation coefficient = 0.76) and better than between each scale and the CHEOPS. Although the DESS showed better inter-rater agreement, it was more dependent on familiarity with the child and was judged more difficult to use by all observers. The NCCPC-PV was the easiest use and the most appropriate for rating the child's pain. CONCLUSION: The NCCPC-PV was the easiest to use for pain assessment in cognitively impaired children and should be adopted in clinical settings.

Hematopoietic stem cell transplantation effects on spinal cord compression in Hurler. - Ferrara, Giovanna; Maximova, Natalia; Zennaro, Floriana; Gregori, Massimo; Tamaro, Paolo (Pediatr Transplant, 2014)
Hurler syndrome type 1 (MPS-1) is an autosomal recessive lysosomal disorder due to the deficiency of the enzyme alpha-L-iduronidase which is necessary for the degradation of dermatan and heparan sulfate. It is characterized by deposit of glycosaminoglycans in tissues, progressive multisystem dysfunction, and early death. HSCT for children with MPS-I is effective, resulting in increased life expectancy and improvement of clinical parameters. The spinal MRI performed on a female 10 yr old undergoing HSCT at the age of 18 months and receiving ERT revealed a considerable decrease in soft tissue around the tip of odontoid causing a significant reduction in spinal cord compression. In light of this result, we suppose that combined ERT and HSCT are successful in Hurler I disease.
Keywords: Bone Marrow Transplantation; Child; Enzyme Replacement Therapy; Female; Glycosaminoglycans; Hematopoietic Stem Cell Transplantation; Humans; Iduronidase; Magnetic Resonance Imaging; Mucopolysaccharidosis I; Odontoid Process; Spinal Cord Compression; Treatment Outcome

A precordial rub in a boy with a severe attack of ulcerative colitis. - Badina, Laura; Ferrara, Giovanna; Guastalla, Pierpaolo; Barbi, Egidio (Pediatr Emerg Care, 2014)
A case of a pneumomediastinum mimicking a pericarditis in a boy with an occult perforation due to ulcerative colitis is reported. Pneumomediastinum is a rare complication of severe attacks of ulcerative colitis, with or without the previous development of a toxic megacolon, that should be considered in the differential diagnosis.
Keywords: Adolescent; Colitis, Ulcerative; Diagnosis, Differential; Humans; Intestinal Perforation; Male; Mediastinal Emphysema; Pericarditis; Radiography, Thoracic